2021
DOI: 10.11606/0103-2070.ts.2021.185622
|View full text |Cite
|
Sign up to set email alerts
|

Two forms of transnational organizing: Mapping the strategies of Global Union Federations

Abstract: It has become a commonplace belief among academics and trade union officials that globalization has weakened trade unions. However, the expansion of global capital has also led to a rise of transnational labor organizing. Since the 2000s, Global Union Federations have developed different strategies to tackle the challenges of globalization. In this article, we analyze two such forms of transnational organizing: A network-based and an event-based form of organizing. While the network-based approach brings toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Without local and national struggles and unionisation, transnational campaigns and organising efforts remain weak and lose momentum. Gains can be consolidated, as many studies show, only by locally organised forces and their pressure on lead firms and local management to adhere to labour standards and on (sub-)national authorities to enforce them (Wells 2009;Ryland 2016;Schmalz et al 2021). Studies further suggest different targets of struggles: while Northern advocacy campaigns mostly target lead firms or big buyers and are oriented towards large consumer markets, Southern labour confronts local authorities, on the firm and state level (Wells 2009).…”
Section: Politics Of Scale: Empirical Insights Into Complex Realitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Without local and national struggles and unionisation, transnational campaigns and organising efforts remain weak and lose momentum. Gains can be consolidated, as many studies show, only by locally organised forces and their pressure on lead firms and local management to adhere to labour standards and on (sub-)national authorities to enforce them (Wells 2009;Ryland 2016;Schmalz et al 2021). Studies further suggest different targets of struggles: while Northern advocacy campaigns mostly target lead firms or big buyers and are oriented towards large consumer markets, Southern labour confronts local authorities, on the firm and state level (Wells 2009).…”
Section: Politics Of Scale: Empirical Insights Into Complex Realitiesmentioning
confidence: 99%
“…states or lead firms) to intervene or influence behaviours of employers or authorities (Merk 2009). Research reveals a banal but cogent truth: success cannot be achieved without local organising but is strongest if organising is multi-scalar (Munck 2021;Schmalz et al 2021). Hence, transnational activism should not be seen as a panacea but as an opportunity structure which can potentially provide local actors with additional sources of power (McCallum 2013;Zajak et al 2017).…”
Section: Politics Of Scale: Empirical Insights Into Complex Realitiesmentioning
confidence: 99%
“…Ford and Gillan (2015) identified several domains of GUF activity, namely knowledge production and dissemination, education and training, engagement with different global institutions, internationalization of local conflicts, supporting the establishment and growth of unions and union networks, and creating new spaces for supranational regulation. More recently, Schmalz et al (2021) have suggested three 'fields of action,' namely global framework agreements, organizing and engagement in local struggles, and efforts to exercise influence on national-level labour laws and regulation.…”
Section: Repertoires Of Action and The Positionality Of Gufsmentioning
confidence: 99%
“…Having tried to target construction projects linked to the 2010 Commonwealth Games, BWI had more success in its initial engagement with the International Federation of Association Football (Fédération Internationale de Football Association, FIFA) in the lead-up to the 2010 South African World Cup, negotiating an agreement under which unions would be involved in joint inspections of construction sites and secured a 12% increase in wages for 70,000 workers (BWI General Secretary, interview 2015). Buoyed by this success, BWI organized a campaign that ultimately led to gains in collective bargaining and the recruitment of close to 22,000 new union members and five new affiliates in the lead-up to the 2014 Brazil World Cup (Building and Wood Workers International BWI, 2017b; see also Schmalz et al, 2021).…”
Section: The Bwi Sports Campaignmentioning
confidence: 99%
See 1 more Smart Citation